Amelioration of Ambient Particulate Matter (PM2.5)-Induced Lung Injury in Rats by Aerobic Exercise Training - Qin, Fei; Fan, Zhengzheng; Xu, Minxiao; Wang, Zhongwei; Dong, Yanan; Qu, Chaoyi; Cui, Shuqiang; Zhao, Lina; Zhao, Jiexiu (Frontiers in Physiology, 2021)
Ambient particulate matter (PM2.5), as an inflammation-inducing factor, increases the prevalence of lung injury. The aim of this study was to examine the protective effect and mechanism of aerobic exercise on PM2.5 exposure-induced lung injury. Forty Wistar rats were randomly divided into four groups: sedentary + PM2.5 exposure, exercise + PM2.5 exposure, sedentary, and exercise groups. All rats in the exercise-related groups underwent 8-week aerobic interval treadmill training (5 days week−1, 1 h day−1). PM-exposed rats were exposed to ambient PM2.5 (6 h day−1) for 3 weeks after the 8-week exercise intervention. Then, ventilation function, histopathological changes, and inflammation responses of pulmonary tissue were examined. Results showed that PM2.5 exposure induced lung injury as manifested by decreased pulmonary function, abnormal histopathological changes, and increased pro-inflammatory cytokine levels (tumor necrosis factor-α and Interleukin-1α). Aerobic exercise alleviated the airway obstruction, reduced respiratory muscle strength, bronchial mucosal exfoliation, ultrastructure damage, and inflammatory responses induced by PM2.5 in exercise-related groups. The benefits of exercise were related with the downregulation of p38–mitogen-activated protein kinase, and the subsequent inhibition of the pathways of the cyclooxygenase 2 product, prostaglandin E2. Thus, pre-exercise training may be an effective way to protect against PM2.5-induced lung inflammatory injury in rats.